Friendly foes: The evolution of host protection by a parasite. Issue 4 (1st September 2017) - Ashby, Ben; King, Kayla C.
Abstract: Hosts are often infected by multiple parasite species, yet the ecological and evolutionary implications of the interactions between hosts and coinfecting parasites are largely unknown. Most theoretical models of evolution among coinfecting parasites focus on the evolution of virulence, but parasites may also evolve to protect their hosts by reducing susceptibility (i.e., conferring resistance) to other parasites or reducing the virulence of coinfecting parasites (i.e., conferring tolerance). Here, we analyze the eco-evolutionary dynamics of parasite-conferred resistance and tolerance using coinfection models. We show that both parasite-conferred resistance and tolerance can evolve for a wide range of underlying trade-offs. The shape and strength of the trade-off qualitatively affects the outcome causing shifts between the minimisation or maximization of protection, intermediate stable strategies, evolutionary branching, and bistability. Furthermore, we find that a protected dimorphism can readily evolve for parasite-conferred resistance, but find no evidence of evolutionary branching for parasite-conferred tolerance, in general agreement with previous work on host evolution. These results provide novel insights into the evolution of parasite-conferred resistance and tolerance, and suggest clues to the underlying trade-offs in recent experimental work on microbe-mediated protection. More generally, our results highlight the context dependence of host-parasite relationships in complex communities.